2019
DOI: 10.1177/0963721419850134
|View full text |Cite
|
Sign up to set email alerts
|

The Sound Symbolism of Names

Abstract: A wealth of research demonstrates that certain language sounds seem to go better with certain kinds of targets (i.e., sound-symbolic associations). The most well-known example is the maluma-takete effect, in which nonwords such as maluma are judged as good matches for round shapes, whereas nonwords such as takete are judged as good matches for sharp shapes. Most of this research involves nonwords, but recent work has shown that sound symbolism has implications for real first names. On the basis of a name’s sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 27 publications
1
7
1
Order By: Relevance
“…Size and shape are two major topics of exploration on sound symbolism ( Sidhu and Pexman, 2017 , 2019 ). In addition to size and shape, there are other perceptual dimensions that have been demonstrated to participate in sound symbolic associations, which include, but are not limited to, hardness, weight, brightness, and even personal characteristics ( Uemura, 1965 ; Kawahara et al, 2018 ; Sidhu and Pexman, 2019 ; Uno et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Size and shape are two major topics of exploration on sound symbolism ( Sidhu and Pexman, 2017 , 2019 ). In addition to size and shape, there are other perceptual dimensions that have been demonstrated to participate in sound symbolic associations, which include, but are not limited to, hardness, weight, brightness, and even personal characteristics ( Uemura, 1965 ; Kawahara et al, 2018 ; Sidhu and Pexman, 2019 ; Uno et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Size and shape are two major topics of exploration on sound symbolism ( Sidhu and Pexman, 2017 , 2019 ). In addition to size and shape, there are other perceptual dimensions that have been demonstrated to participate in sound symbolic associations, which include, but are not limited to, hardness, weight, brightness, and even personal characteristics ( Uemura, 1965 ; Kawahara et al, 2018 ; Sidhu and Pexman, 2019 ; Uno et al, 2020 ). However, in most previous studies of sound symbolism, the focus has been exclusively on the five senses (visual, auditory, tactile, olfactory, and gustatory), with a heavy emphasis on visual properties, such as size and shape.…”
Section: Introductionmentioning
confidence: 99%
“…There are other semantic properties which have been shown to be signaled via sound symbolism, including color, brightness, taste, weight, strength, etc. (Jakobson, 1978;Lockwood and Dingemanse, 2015;Westbury et al, 2018;Winter et al, 2019;Kawahara and Kumagai, 2021, among others), but it remains to be explored precisely what kinds of semantic concepts can be signaled via sound symbolism in natural languages, and relatedly, how complex such concepts can be (Lupyan and Winter, 2018;Westbury et al, 2018;Sidhu and Pexman, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Emotional features are also connected to linguistic information [ 10 ]. In addition to sound-symbolic associations between pseudowords (new words) and referents, real words can be sound symbolically associated with perceptual or abstract features [ 11 , 12 ]. Previous findings suggested that the oral shapes to pronounce linguistic features were associated with perceptual and emotional features [ 5 , 13 ], whereas written linguistic features (alphabetic letters and other characters) were also associated with them [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%